Global maximum power point tracking using variable sampling time and p-v curve region shifting technique along with incremental conductance for partially shaded photovoltaic systems. (1st September 2019) - Kumar, Rajneesh; Khandelwal, Subodh; Upadhyay, Prashant; Pulipaka, Subrahmanyam
Graphical abstract: Highlights: A modified INC using p-v curve region shifting based MPPT algorithm is developed to track global power peak under partial shading conditions. Modeling of SEPIC converter is described to implement an adaptive variable sampling time for faster operation of proposed tracking algorithm under partial shading conditions. Irradiance forecast is also introduced in MPPT algorithm flow chart to decide the starting point on p-v curve from where the tracking begins. Proposed algorithm is validated on TMS320F28027 LAUNCHPAD using Process-In-the-Loop approach for practical applications. Abstract: This paper proposes modifications to Incremental Conductance (INC) concept to track global maximum power point under partial shading conditions of photovoltaic (PV) systems. The proposed algorithm determines the p-v curve as a combination of regions, and tracks global peak by shifting operating point from one region to another without using any nature inspired intelligent techniques like particle swarm optimization (PSO) and other related algorithms. Additionally, a variable sampling time concept is introduced in the algorithm for faster tracking of global peak under extreme partial shading conditions arising due to random shading pattern of PV modules. MATLAB /SIMULINK platform was used to model PV module in conjunction with SEPIC converter for battery charging application. Proposed algorithm was tested under different shading patterns to observe the tracking speed and accuracy of the tracker. Finally, the concept behind proposed algorithm was validated on TMS320F28027 LAUNCHPAD DSP board using Process-in- loop (PIL) approach for practical applications. Results demonstrate the usefulness of proposed algorithm in terms of less computational time as compared to latest reported work in this field.